Relations of Antiretroviral Combinations to CD4 Levels of HIV TB Patiens in RSUD H.Abdul Manap Jambi: Hubungan Kombinasi Antiretroviral Terhadap Kadar CD4 Pasien HIV TB Rawat Jalan RSUD H. Abdul Manap Jambi - Permatasari, Jelly; Meirista, Indri; Bafadhal, Hamira (Journal of Pharmacy and Science, 2021)
The cases of Human Immunodeficiency Virus (HIV) infection are increasing every year. This case is a disease that is very rapidly transmitted throughout the world. HIV increases the risk of developing tuberculosis (TB) and conversely TB infection increases HIV progression. In 2017, it is estimated that 10 million people have HIV TB. Combination of antiretrovirals is the basis for the management of antiretroviral therapy for HIV / AIDS patients, because it can reduce resistance, suppress HIV replication effectively so that transmission, opportunistic infections and other complications. The purpose of this study was to determine the relationship between antiretroviral combinations and CD4 levels in outpatient HIV TB patients at RSUD H. Abdul Manap Jambi. This study is a retrospective cohort study using medical records of outpatient HIV TB patients at RSUD H. Abdul Manap Jambi based on inclusion and exclusion criteria. Based on research conducted on outpatient HIV TB patients at Abdul Manap Hospital, Jambi, it was found that there was no relationship between antiretroviral combinations and CD4 levels in HIV TB patients, marked by Asimp.Sig 0.778> 0.05.